The extent of cereal cultivation among the Bronze Age to Turkic period societies of Kazakhstan determined using stable isotope analysis of bone collagen. (July 2015) - Motuzaite Matuzeviciute, G.; Lightfoot, E.; O'Connell, T.C.; Voyakin, D.; Liu, X.; Loman, V.; Svyatko, S.; Usmanova, E.; Jones, M.K.
Abstract: This paper explores the contribution of plant foods to the diet of presumed pastoral societies in Kazakhstan. Carbon and nitrogen stable isotope analysis, together with radiocarbon dating, was carried out on human and animal bones from 25 Chalcolithic, Bronze Age, Early Iron Age, Hunic and Turkic sites across Kazakhstan. We use these data to examine dietary differences across time and space within and between populations. Our results show that at the Bronze Age sites of mountainous southern Kazakhstan people consumed C4 plants, likely domesticated millets ( Panicum miliaceum and Setaria italica ) as supported by previously published archaeobotanical direct evidence. By dating individuals with high δ 13 C values we find the earliest evidence to date of the consumption of large quantities of millet in Central Asia. By contrast, there is little input of C4 plants to diets of individuals dating to the Bronze Age from northern Kazakhstan. Stable isotope data from later periods show that from the Early Iron Age and continuing through to the Turkic period, C4 plants were a major component of the human food web across the region. The wide variety of stable isotope results, both within and between contemporary sites from the southern regions of Kazakhstan, indicates a diversity of food choice. Highlights: This paper is the first stable isotope study embracing the regions of the southern Kazakhstan. This paper shows the importance of plant foods to the diet of pastoral societies. Results demonstrate the presence of the established agriculture in S Kazakhstan from 1800 BC. We present the direct AMS dates of individuals along the stable isotope results. We show that mountain regions of the Central Asia were the early pathways crop spread.